Haggard’s Questioning of the Heroic - John Coates (Cahiers Victoriens et Edouardiens, 2009)
Rider Haggard is sometimes thought of as a writer who offered thrilling incidents, racial stereotypes and imperialist propaganda, or as a naïve myth-maker, unlocking his subconscious and reaching out to ours. Concentrating on ‘Eric Brighteyes’ (1891) and ‘Narda the Lily’ (1892), this paper argues that Haggard was far more nuanced and self-aware than is commonly supposed. The two novels explore his misgivings about the warrior ethic and competitive heroic societies.